A standardized extract of Coleus forskohlii root protects rats from ovariectomy-induced loss of bone mass and strength, and impaired bone material by osteogenic and anti-resorptive mechanisms - Kulkarni, Chirag; Sharma, Shivani; Porwal, Konica; Rajput, Swati; Sadhukhan, Sreyanko; Singh, Vaishnavi; Singh, Akanksha; Baranwal, Sanjana; Kumar, Saroj; Girme, Aboli; Pandey, Alka Raj; Singh, Suriya Pratap; et al. (Frontiers in Endocrinology, 2023)
Introduction: In obese humans, Coleus forskohlii root extract (CFE) protects against weight gain owing to the presence of forskolin, an adenylate cyclase (AC) activator. As AC increases intracellular cyclic adenosine monophosphate (cAMP) levels in osteoblasts that has an osteogenic effect, we thus tested the skeletal effects of a standardized (CFE) in rats. Methods: Concentrations of forskolin and isoforkolin were measured in CFE by HPLC. CFE and forskolin (the most abundant compound present in CFE) were studied for their osteogenic efficacy in vitro by alkaline phosphatase (ALP), cAMP and cyclic guanosine monophosphate (cGMP) assays. Femur osteotomy model was used to determine the osteogenic dose of CFE. In growing rats, CFE was tested for its osteogenic effect in intact bone. In adult ovariectomized (OVX) rats, we assessed the effect of CFE on bone mass, strength and material. The effect of forskolin was assessed in vivo by measuring the expression of osteogenic genes in the calvarium of rat pups. Results: Forskolin content in CFE was 20.9%. CFE increased osteoblast differentiation and intracellular cAMP and cGMP levels in rat calvarial osteoblasts. At 25mg/kg (half of human equivalent dose), CFE significantly enhanced calcein deposition at the osteotomy site. In growing rats, CFE promoted modelling-directed bone formation. In OVX rats, CFE maintained bone mass and microarchitecture to the level of sham-operated rats. Moreover, surface-referent bone formation in CFE treated rats was significantly increased over the OVX group and was comparable with the sham group. CFE also increased the pro-collagen type-I N-terminal propeptide:rat cross-linked C-telopeptide of type-I collagen (PINP:CTX-1) ratio over the OVX rats, and maintained it to the sham level. CFE treatment decreased the OVX-induced increases in the carbonate-to-phosphate, and carbonate-to-amide-I ratios. CFE also prevented the OVX-mediated decrease in mineral crystallinity. Nanoindentation parameters including modulus and hardness were decreased by OVX but CFE maintained these to the sham levels. Forskolin stimulated ALP, cAMP and cGMP in vitro and upregulated osteogenic genes in vivo. Conclusion: CFE likely due to the presence of forskolin displayed a bone conserving effect via the osteogenic and anti-resorptive mechanisms resulting in the maintenance of bone mass, microarchitecture, material, and strength.